2018
DOI: 10.1186/s13073-018-0562-1
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic profiling of non-small cell lung cancer xenografts uncover LRP12 DNA methylation as predictive biomarker for carboplatin resistance

Abstract: BackgroundNon-small cell lung cancer (NSCLC) is the most common cause of cancer-related deaths worldwide and is primarily treated with radiation, surgery, and platinum-based drugs like cisplatin and carboplatin. The major challenge in the treatment of NSCLC patients is intrinsic or acquired resistance to chemotherapy. Molecular markers predicting the outcome of the patients are urgently needed.MethodsHere, we employed patient-derived xenografts (PDXs) to detect predictive methylation biomarkers for platin-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 75 publications
0
31
0
1
Order By: Relevance
“…The aforementioned genomic, transcriptional and proteomic study results indicate that the molecular characteristics of cancer cells in PDX models may change during engraftment. A recent NSCLC study suggested that the epigenome may evolve: the genome‐wide DNA methylation profile of xenograft tumors was poorly correlated with that of parental tumors . However, none of these studies have accounted for the constantly changing phenotype .…”
Section: Differences In Molecular Characteristics Among Pdx Modelsmentioning
confidence: 99%
“…The aforementioned genomic, transcriptional and proteomic study results indicate that the molecular characteristics of cancer cells in PDX models may change during engraftment. A recent NSCLC study suggested that the epigenome may evolve: the genome‐wide DNA methylation profile of xenograft tumors was poorly correlated with that of parental tumors . However, none of these studies have accounted for the constantly changing phenotype .…”
Section: Differences In Molecular Characteristics Among Pdx Modelsmentioning
confidence: 99%
“…The patient-derived xenograft (PDX) model of cancer is created by transplanting tumor tissue in immunodeficient mice at the same (orthotopic) or different (ectopic) anatomic site. PDXs retain genetic, transcriptional and phenotypic features of the original tumor even after long-term continuous passage in vivo [16][17][18][19][20][21], and they have been used successfully to develop new therapies for cancers [22,23]. Subcutaneous breast cancer PDXs are often used for pre-clinical drug screening because both tumor transplantation and tumor tracking are easy.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms responsible for resistance to chemotherapy are complex, and are related to several factors, such as drug uptake, cell cycle, DNA repair and others; the molecular mechanisms responsible for chemotherapeutic resistance have not yet been fully elucidated (18,19). Recently, it was found that the abnormal DNA methylation of the genome plays an important role in the chemotherapy resistance of cancers, including NSCLC (20,21). It was found that platinum-based chemotherapy can influence DNA methylation modification in cancer (22).…”
Section: Discussionmentioning
confidence: 99%